Digital Governance and the Reconfiguration of Religious Authority in Post-Secular Indonesia: The Emergence of Digital Faith as Mediated Authority - Zakaria Efendi; Meysellaa Al Firdha Hanim; Zaenuddin Hudi Prasojo; Lutse Lambert Daniel Morin; Febi Setiyawati (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2026)
Post-secular Indonesia, where 229.4 million internet users coexist within an 87% Muslim population, presents a paradigmatic site for examining how digital governance reshapes religious authority. As digital infrastructure expands, tensions between traditional religious legitimacy and state-regulated algorithmic mechanisms intensify, yet the tripartite interaction among state regulation, platform architecture, and religious community agency remains theoretically underspecified. This study aims to analyse the dynamics of religious authority reconfiguration within Indonesia’s digital governance ecosystem, examining how these interactions produce, contest, and transform Islamic religious legitimacy in the digital age. Employing Fairclough’s Critical Discourse Analysis three-stage model text analysis (2013), discursive practice analysis, and socio-cultural practice analysis, this study analysed five categories of digital regulatory frameworks comprising legal instruments, administrative policies, and algorithmic control mechanisms. Data were collected from June to October 2025 through systematic retrieval of regulatory documents, institutional statements, and civil society monitoring reports. The findings reveal three key dynamics: state regulatory instruments function as mechanisms of discursive power repositioning religious authority from traditional institutions toward technocratic governance; hybrid forms of legitimacy emerge from the interaction between state, platforms, and religious actors; and digital communities negotiate and contest state control through performative engagement that constructs alternative truth regimes. This study concludes that digitisation fundamentally transforms both religious practices and the epistemological foundations of authority, captured in the concept of digital faith as mediated authority. This article contributes to the intersecting fields of digital religion, post-secular governance, and platform society studies by offering an integrative analytical model grounded in the Global South context, a dimension underrepresented in existing scholarship.